EPIDEMIOLOGY OF ESOPHAGEAL CANCER, RISK FACTORS AND POSSIBILITIES FOR PREVENTION - Bjelakovic, Milica; Benedeto Stojanov, Daniela; Bjelaković, Marko; Golubović, Ivana; Gmijović, Marko (Acta medicae Medianae, 2022)
The incidence and mortality of esophageal cancer in developed countries increased in the last four decades, as opposed to the reduced incidence and mortality of other cancers. Esophageal cancer is the eighth most common and the sixth leading cause of cancer death in the world. In the last 3 decades, there has been a shift in the leading histological type of esophageal cancer in developed countries from esophageal squamous cell to esophageal adenocarcinoma. Risk factors lead to the appearance of precancerous conditions, squamous dysplasia as a precursor of esophageal squamous cell carcinoma and Barrett's esophagus as a precursor of esophageal adenocarcinoma. Tobacco, alcohol, hot Mate drink and pickled vegetables are associated with increased risk of esophageal cancer, while increased fruit and vegetable intake could have a preventive effect on esophageal cancer. The evidence about the influence of distal esophageal sphincter relaxants and histamine 2 receptor antagonists is contradictory. There is an inverse association of Helicobacter pylori infection and Barrett's esophagus and esophageal adenocarcinoma. We have low certainty evidence about the effect of infection with human papilloma virus and different chemical carcinogens like polycyclic aromatic hydrocarbons, N-nitroso compounds, acetaldehyde, and fumonisins on esophageal cancer. A number of predisposing conditions like gastro-esophageal reflux disease, Barrett's esophagus, obesity, hiatal hernia, achalasia, tylosis, and Plummer Vinson syndrome may increase the risk of esophageal cancer. Primary prevention of esophageal cancer consists of lifestyle changes like smoking cessation, stopping of alcohol consumption and increased intake of fruits and vegetables. Secondary prevention consists of chemoprevention, screening and monitoring program.
Keywords: esophageal cancer, risk, prevention